Identification of an immunodominant region of Fel d 1 and characterization of constituent epitopes. - Bateman, E; Ardern-Jones, MR; Ogg, G (2008)
BACKGROUND: Characterization of T cell epitopes restricted by common HLA alleles is a powerful tool in the understanding of the immune responses to allergens and for the identification of potential peptides for future peptide immunotherapy (PIT). One important requirement is the identification and use of peptides that will bind to HLA molecules covering a large proportion of the population. OBJECTIVE: To identify commonly recognized CD4(+) T cell epitopes in Fel d 1, restricted through frequently expressed HLA molecules for potential future use in PIT. METHODS: HLA matched antigen presenting cells, HLA blocking antibodies, and peptide truncations were used in ELISpot assays to establish HLA-restricted T cell epitopes. Cytokine responses were measured by ex vivo and cultured IFN-gamma, IL-4, and IL-10 ELISpots. RESULTS: Responses to an immunodominant region of chain 2 were identified in the majority of atopic individuals and epitopes restricted by HLA-DQB1(*)06 and -DPB1(*)0401 were characterized in detail. Significantly higher ex vivo IL-4 and lower IFN-gamma responses were observed to both epitopes in individuals with atopic dermatitis (AD) compared with those without disease. IL-10 responses were significantly lower in those with AD in the individuals with HLA-DPB1(*)0401. CONCLUSIONS: We have identified an immunodominant region of Fel d 1 which is frequently recognized by CD4(+) T cells from atopic individuals and contains epitopes that are restricted by very common HLA alleles.